Development Of Pop Up Book Media Sub Theme Technology Development Of Clothing Production To Train Writing Skills In Class III Elementary School Students - Sa’adah, Sufi Ikrima; Wibowo, Satrio; Rahmawati, Ery (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
In the development of this Pop Up Book media using 7 procedures, namely potential and problems, from the results of potential and problems then the researcher conducts and makes a data collection, from the data collection the researcher makes a design design that will be validated by media experts and if there is a revision it will be corrected immediately, after that it will be tested, if there are still deficiencies it will be revised again so that the resulting product is ready to be used in learning. The development of this Pop Up Book media aims to train the writing skills of third grade elementary school students. Research and Development (R&D) is the method that will be used in this research by using pretest-posttest. In this study, the subjects used were third grade students in the 2021/2022 academic year, totaling 14 students as controls and 14 students as experimenters. Learning outcomes after using Pop Up Book media obtained the final results online for each class, namely in the control class, namely 47%, which is stated in the control class is included in the category of "Less Effective" class with conventional learning methods or lectures. Furthermore, the experimental class is a class that uses a learning method using top-up book media, a score of 86% is obtained. This proves that the Pop Up Book used as a medium at SDN WAGE 1 Class III after learning by utilizing the Pop Up Book learning media is stated in the criteria "Effective".Keywords: Pop Up Book; Development of clothing production technology; writing skillsAbstrak: Dalam pengembangan media Pop Up Book ini menggunakan 7 prosedur yaitu potensi dan masalah, dari hasil potensi dan masalah selanjutnya peneliti melakukan dan membuat kumpulan data, dari kumpulan data tersebut peneliti membuat rancangan desain yang akan divalidasi oleh ahli media dan jika terdapat revisi akan segera diperbaiki, setelah itu akan diuji coba, jika masih terdapat kekurangan akan direvisi Kembali sehingga produk yang dihasilkan siap digunakan dalam pembelajaran. Pengembangan media  Pop Up Book ini bertujuan untuk melatih keterampilan menulis siswa kelas III SD. Research and Development (R&D) adalah metode yang akan digunakan dalam penelitian ini dengan menggunakan pretest-posttest. Dalam penelitian ini subjek yang digunakan yaitu siswa kelas III Tahun Pelajaran 2021/2022 yang berjumlah 14 siswa sebagai control dan 14 siswa sebagai eksperimen. Hasil belajar setelah menggunakan media Pop Up Book didapat hasil akhir daring masing-masing kelas yakni pada kelas kontrol yakni 47%, dimana dinyatakan pada kelas kontrol adalah termasuk kedalam kategori “Kurang Efektif” kelas dengan metode pembelajaran konvensional atau ceramah. Selanjutnya pada kelas eksperimen merupakan kelas yang menggunakan metode pembelajaran menggunakan media top-up book didapat nilai sebanyak 86% Hal tersebut membuktikan Pop Up Book yang digunakan sebagai media di SDN WAGE 1 Kelas III setelah adanya pembelajaran dengan memanfaatkan media pembelajaran Pop Up Book dinyatakan dalam kriteria “Efektif”.Kata kunci: Pop Up Book; Perkembangan teknologi produksi sandang; keterampilan menulis